Makna dan Fungsi Bangunan Rumah Adat Loro Dirma di Desa Sanleo Kecamatan Malaka Timur Kabupaten Malaka - Merliana De Carvalho Asa; Yohanis Kristianus Tampani; Clotilde Seran; Antonius Bere (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The Loro Dirma Traditional House in Sanleo Village is an important representation of the culture of the indigenous people and is the center of the formation of social, spiritual, and local wisdom identities. This study aims to: (1) describe the structure and architecture of the Loro Dirma Traditional House, and (2) analyze the symbolic meaning contained therein in the context of the life of the indigenous people. The study uses a descriptive qualitative approach through direct observation, documentation, and in-depth interviews with traditional leaders and the local community. The results of the study indicate that the Loro Dirma architecture is full of philosophy that reflects the values ​​of unity, respect for ancestors, and the concept of balance between humans, nature, and the Creator. In addition, the function of Loro Dirma has undergone a transformation, from a traditional residence to a center for traditional activities, a space for deliberation, the implementation of religious ceremonies, and a medium for educating cultural values ​​for the younger generation. However, the study found challenges in preservation efforts, such as limited traditional raw materials, changes in community lifestyles, and the declining interest of the younger generation in local culture. Therefore, collaboration between local governments, indigenous communities, and educational institutions is needed to document, revitalize, and integrate Loro Dirma cultural values ​​into formal and non-formal curricula to ensure their sustainability.